Community Perspectives on Socio-Economic Impacts and Conservation Effectiveness at Melaka World Heritage Site - Prasad Thirunavukkarasu,; Indera Syahrul Mat Radzuan ,; Zarina Shamsudin,; Seow Ta Wee,; Yahaya Ahmad, (Journal of Social Transformation and Regional Development, 2025)
The effective design of policies, programmes, and projects (3Ps) requires a thorough understanding of their implementation, particularly in achieving intended objectives and assessing their socio-economic impacts on local communities. However, evaluations of such initiatives remain limited, including within the context of heritage sites such as Melaka. This study investigates local communities' perspectives on the socio-economic impacts of World Heritage Site (WHS) designation and the effectiveness of conservation efforts in Melaka, Malaysia. Utilising a mixed-methods approach, the study incorporates quantitative survey data from 386 respondents, analysed using SPSS, alongside qualitative insights from interviews, examined through thematic analysis. The findings reveal that enhanced community pride is a key positive outcome, whereas traffic congestion is the most frequently reported negative consequence. While authorities are generally perceived favourably, concerns persist regarding insufficient community involvement in decision-making processes. The study highlights the critical need for integrating local perspectives more effectively in the early stages of 3P implementation to ensure sustainable heritage management and community well-being.